Self-harm in university students: A comparative analysis of data from the Multicentre Study of Self-harm in England - Clements, C; Farooq, B; Hawton, K; Geulayov, G; Casey, D; Waters, K; Ness, J; Kelly, S; Townsend, E; Appleby, L; Kapur, N (Elsevier, 2023)
Background: Increases in poor mental health and suicide have been identified among university students in the UK. However, little is known about self-harm in this group. Aims: To describe and identify care needs of university aged-students who self-harm via comparisons with an age-equivalent non-student group who self-harm. Methods: Observational cohort data from The Multicentre Study of Self-harm in England were used to investigate students aged 18 to 24 years who presented to emergency departments for self-harm, 2003 to 2016. Data were collected via clinician reports and medical records from five hospitals in three English regions. Characteristics, rates, repetition, and mortality outcomes were investigated. Results: The student sample included 3491 individuals (983, 28.2 % men; 2507, 71.8 % women; 1 unknown) compared to 7807 (3342, 42.8 % men; 4465, 57.2 % women) non-students. Self-harm increased over time in students (IRR 1.08, 95%CI 1.06–1.10, p < 0.01) but not in non-students (IRR 1.01, 95%CI 1.00–1.02, p = 0.15). There were differences in monthly distribution of self-harm with more presentations by students in October, November, and February. Characteristics were broadly similar, but students reported more problems with studying and mental health. Repetition (HR 0.78, 95%CI 0.71–0.86, p < 0.01) and mortality (HR 0.51, 95%CI 0.33–0.80, p < 0.01) were lower in students than non-students. Conclusions: Self-harm in students may be directly related the student experience, such as academic pressure, relocation, and the transition to independent living. Wellbeing initiatives targeting these factors, alongside mental health awareness training for academic and non-academic staff may help to support students at risk.